MENINGKATKAN NILAI TUGAS PROYEK TEMA UDARA BERSIH BAGI KESEHATAN MELALUI KEGIATAN PROJECT BASED LEARNING SISWA KELAS V - Syamsiah Syamsiah (Jurnal Pendidikan dan Pembelajaran Sekolah Dasar (JPPSD), 2022)
This study uses a classroom action research model that is in the form of a spiral from one cycle to the next. Each cycle includes planning (plan), action (action), observation (observation), and reflection (reflection), consisting of three cycles, each cycle there are 3 meetings for giving action and 1 time giving the end of the cycle test. The results show that: ( 1) The value of project assignments is cycle three, the average score is 83.37 in the good category, the second cycle has an average score of 72.11 in the less category, the first cycle is 70.26 in the less category, increasing by 11.26% better in cycle three than in cycle two. (2) Positive support for teacher ability in cycle three is 79.17% good, cycle two is 61.11% sufficient, cycle one is 54.17% sufficient, cycle three quality is in accordance with indicators of research success. (3) Positive support for student learning activities in cycle three is 86.84% very good, cycle two is 60.23% is sufficient, cycle one is 59.06% is sufficient. The conclusion of this study is that through project based learning activities, it can increase the value of the project task on the theme of clean air for health.